Breathing can be dangerous: Opportunistic fungal pathogens and the diverse community of the small mammal lung mycobiome - Salazar-Hamm, Paris S.; Montoya, Kyana N.; Montoya, Liliam; Cook, Kel; Liphardt, Schuyler; Taylor, John W.; Cook, Joseph A.; Natvig, Donald O. (Frontiers in Fungal Biology, 2022)
Human lung mycobiome studies typically sample bronchoalveolar lavage or sputum, potentially overlooking fungi embedded in tissues. Employing ultra-frozen lung tissues from biorepositories, we obtained fungal ribosomal RNA ITS2 sequences from 199 small mammals across 39 species. We documented diverse fungi, including common environmental fungi such as Penicillium and Aspergillus, associates of the human mycobiome such as Malassezia and Candida, and others specifically adapted for lungs (Coccidioides, Blastomyces, and Pneumocystis). Pneumocystis sequences were detected in 83% of the samples and generally exhibited phylogenetic congruence with hosts. Among sequences from diverse opportunistic pathogens in the Onygenales, species of Coccidioides occurred in 12% of samples and species of Blastomyces in 85% of samples. Coccidioides sequences occurred in 14 mammalian species. The presence of neither Coccidioides nor Aspergillus fumigatus correlated with substantial shifts in the overall mycobiome, although there was some indication that fungal communities might be influenced by high levels of A. fumigatus. Although members of the Onygenales were common in lung samples (92%), they are not common in environmental surveys. Our results indicate that Pneumocystis and certain Onygenales are common commensal members of the lung mycobiome. These results provide new insights into the biology of lung-inhabiting fungi and flag small mammals as potential reservoirs for emerging fungal pathogens